What factors best explain attitudes to snow leopards in the Nepal Himalayas? - Hanson, Jonathan H.; Schutgens, Maurice; Leader-Williams, Nigel (PLOS ONE, 2019)
The snow leopard Panthera uncia is a vulnerable wild felid native to mountainous regions of 12 Asian countries. It faces numerous overlapping threats, including killings by herders retaliating against livestock losses, the illegal wildlife trade, loss of prey and habitat, infrastructure, energy and mining developments, and climate change. The species ranges over large territories that often lie outside of protected areas (PA), so coexistence with human populations across its range is key to its persistence. Human attitudes to snow leopards may be an important factor to consider in reducing overlapping threats to this species. However, this nexus has not been widely studied to date. Attitudes to snow leopard conservation, including actors and interventions, may also be a significant aspect of coexistence. These have also received limited empirical attention. This study therefore explored human attitudes to snow leopards and to snow leopard conservation, the motivations for these attitudes and the individual factors that best explained them. Using systematic sampling, a quantitative questionnaire was administered to 705 households at two sites in the Nepal Himalayas: Sagarmatha National Park, with a less decentralised governance model, and Annapurna Conservation Area, with a more decentralised model. Linear regression models were the main form of analysis. Based on these, attitudes to snow leopard conservation emerged as the strongest influence on local attitudes to snow leopards, and vice versa. This was true in both PAs, despite their differing management regimes. Other important explanatory factors included numbers of livestock owned, years of education, household livelihoods and age. Furthermore, a positive intrinsic motivation was the most common reason given by respondents to explain their attitudes to both snow leopards and snow leopard conservation. These findings demonstrate that, in addition to the usual suite of factors that influence attitudes to a species, the way in which its conservation is pursued and perceived also needs consideration. How the snow leopard is conserved may strongly influence its coexistence with local communities.